Solar Hot Water System Matter in Turkey (Mersin Case) - Sakinc, Esra; Sozen, Mujgan Serefhanoglu (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2010)
When the effects of sustainability on the construction sector have been taken into consideration, solar active systems on buildings emerge as an important design issue in the context of renewal energy usage. Solar hot water systems such as those widely used in Turkey are inefficient and have a negative effect on a building's aesthetic and the urban view in general because of the poor quality of installation. Natural circulated open loop systems are commonly used, particularly in the south of Turkey, as they are highly economical and require no regulation to install. Solar hot water systems tend to be clustered together on the roofs, causing visual pollution, and this situation arises largely because are not considered part of the architectural design. It is therefore important to consider the negative effects of such systems in the form of treatment studies. This study aims to determine the positive effects that will be gained by the renovation of solar hot water systems in Mersin, a city in the southern region of Turkey.
Keywords: Solar water heating systems; solar architecture; building integrated systems; Architecture